Relationship between parenting styles and academic performance among undergraduates at University Putra Malaysia - Che Hassan, Norlizah; Hew, Min Sen (International Organization Center of Academic Research, 2015)
The purpose of this study was to investigate the relationship between parenting styles and academic performance among undergraduates at Universiti Putra Malaysia (UPM). This study also investigated the relationship between academic performances and undergraduates’ social demographic factors (ethnic group and socioeconomic status). This is a cross sectional survey research, which involved 302 undergraduates from Faculty of Educational Studies at Universiti Putra Malaysia (UPM) selected through cluster sampling method. The instrument of Parenting Authority Questionnaire (PAQ) from Buri (1991) was used to measure undergraduates perceived of parenting style. The collected data was analyzed using Statistical Packages for Social Science (SPSS) version 17.0. The findings showed there was a significant negative relationship between authoritarian parenting style and undergraduates’ academic performance, but no significant relationship between academic performance and the other two parenting style, which were authoritative and permissive parenting style. Chi-square test of independent shows that there was no significant difference in parenting styles among the undergraduates in term of ethnic group as well as socioeconomic status (SES). The present study generally told us every member in a family can be influenced interdependently. This study showed that authoritarian parenting style is negatively related with academic performance. Hence, this study provides and suggests some implication for the family, tertiary education institution and educators.